Implementation of Supply Chain Management for Mineral Water Inventory Management at Putri Store - Rahmadina Rahmadina; Novica Irawati; Rohminatin Rohminatin (Jurnal IPTEK Bagi Masyarakat, 2026)
Putri Store is a retail business that sells mineral water products with relatively high customer demand. However, its inventory management is still conducted manually, causing inaccurate stock records, delays in reordering, and frequent stockouts. Based on observations from August to October 2025, 26 stockout incidents were found across several mineral water products. This study aims to design and implement a web-based Supply Chain Management (SCM) system to improve inventory management effectiveness at Putri Store. The system was developed using the Waterfall method, consisting of requirements analysis, system design, implementation, testing, and evaluation. The system design used Unified Modeling Language (UML) and Entity Relationship Diagram (ERD), while implementation was carried out using PHP and MySQL. System testing was conducted using the Black Box Testing method on the main modules, including login, inventory management, supplier management, ordering, and reporting. The results showed that all system functions operated according to user requirements, achieving a 100% success rate. The developed system supports real-time inventory monitoring, integrates supplier data with the ordering process, and automatically generates inventory reports. Its implementation reduced stock search time from 10–15 minutes to 1–2 minutes and report generation time from 20–30 minutes to less than 5 minutes. User satisfaction reached 93.2%, with an average score of 4.66 out of 5. Therefore, the web-based SCM system effectively improves inventory accuracy, accelerates decision-making, and reduces stockout risks at Putri Store.